Diagnostics of Ebola virus - Aurora Bettini; Daniele Lapa; Anna Rosa Garbuglia (Frontiers in Public Health, 2023)
Ebola is a highly pathogenic virus, which in humans reaches a mortality rate above 50%. Due to a lack of laboratories in territories where Ebola viruses are endemic and the limited number of surveillance programmes, tests for the confirmation of suspected cases of Ebola are often performed in Reference Laboratories. While this provides guarantees regarding the accuracy of results, the shipment of samples to a centralized facility where the diagnostic test can be performed and the time required to achieve the results takes several days, which increases costs and entails delays in the isolation of positive subjects and therapeutic intervention with negative consequences both for patients and the community. Molecular tests have been the most frequently used tool in Ebola diagnosis in recent outbreaks. One of the most commonly used molecular tests is the Real-Star Altona, which targets a conserved area of the L gene. This assay showed different sensitivities depending on the Ebola virus: 471 copies/mL (EBOV) and 2871 copies/ml (SUDAN virus). The Cepheid system also showed good sensitivity (232 copies/mL). The LAMP platform is very promising because, being an isothermal reaction, it does not require high-precision instrumentation and can be considered a Point of Care (PoC) tool. Its analytical sensitivity is 1 copy/reaction. However, since data from real life studies are not yet available, it is premature to give any indications on its feasibility. Moreover, in November 2014, the WHO recommended the development of rapid diagnostic tests (RDT) according to ASSURED criteria. Several RDT assays have since been produced, most of which are rapid tests based on the search for antibody anti-Ebola viral proteins with immunochromatographic methods. Several viral antigens are used for this purpose: VP40, NP and GP. These assays show different sensitivities according to the protein used: VP40 57.4–93.1%, GP 53–88.9% and 85% for NP compared to reference molecular assays. From these results, it can be deduced that no RDT reaches the 99% sensitivity recommended by the WHO and therefore any RDT negative results in suspected cases should be confirmed with a molecular test.